2014
DOI: 10.7257/1053-816x.2014.34.5.252
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Treatment for Women with Stress Urinary Incontinence

Abstract: This was anon-experimental, descriptive, correlational study designed to assess the feasibility and efficacy of an evidence-based online pelvic floor treatment pro gram targeting stress urinary incontinence in adult women. The majority of the participants reported some level of improvement in their incontinence symptoms and overwhelmingly supported the web-based physical therapy program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…For SUI, there is also evidence that an eHealth intervention is effective. Two Swedish randomised controlled trials (one with an internet-based and one with a mobile phone intervention) and one observational feasibility study (internet-based intervention) have been conducted in this area [1719]. The Swedish trials showed that symptom severity and incontinence-related quality of life improved significantly after women received an Internet-based intervention, or a mobile phone app intervention with PFMT [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…For SUI, there is also evidence that an eHealth intervention is effective. Two Swedish randomised controlled trials (one with an internet-based and one with a mobile phone intervention) and one observational feasibility study (internet-based intervention) have been conducted in this area [1719]. The Swedish trials showed that symptom severity and incontinence-related quality of life improved significantly after women received an Internet-based intervention, or a mobile phone app intervention with PFMT [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Internet-based therapy (eHealth) with PFMT might provide a solution to overcoming barriers that prevent women from seeking help. eHealth consisting of a 3-month Web-based intervention with unsupervised PFMT has shown to be effective in improving treatment of incontinence [1315]. A main outcome from a qualitative study on women’s experiences with this eHealth intervention showed they felt that their complaints had been acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…40,58 Of the 5 studies with interventions comprised of one component (n = 5), 2 reported statistically significant improvements in UI symptoms, 31,50 and 3 reported no significant improvements in UI symptoms. 38,56,57 The combination of education, PFME regimen, and bladder training components was the most frequently associated with statistically significant improvements. A focus on the 12 studies using a 2-group randomized controlled trial design or wait list control trial design (see Table 3 symbols) shows that 8 reported a statistically significant difference between groups in UI symptoms.…”
Section: Resultsmentioning
confidence: 96%